2001
DOI: 10.1101/gr.158801
|View full text |Cite
|
Sign up to set email alerts
|

Biased Distribution of Inverted and Direct Alus in the Human Genome: Implications for Insertion, Exclusion, and Genome Stability

Abstract: Alu sequences, the most abundant class of large dispersed DNA repeats in human chromosomes, contribute to human genome dynamics. Recently we reported that long inverted repeats, including human Alus, can be strong initiators of genetic change in yeast. We proposed that the potential for interactions between adjacent, closely related Alus would influence their stability and this would be reflected in their distribution. We have undertaken an extensive computational analysis of all Alus (the database is at http:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 49 publications
(71 reference statements)
6
89
0
Order By: Relevance
“…The efficiency of removal through this mechanism is expected to increase with the size of the LTR (Bennetzen, 2005) and also with an inverse of the length of the intervening sequence, and could well be the mechanism behind the removal of close facing retroelement insertions. In humans, Alu repeats constitute 10% of the genome and even though they have a different mechanism of integration to the copialike retroelements, closely spaced and inverted Alu elements are extremely unstable (Lobachev et al, 2000;Rowold and Herrera, 2000;Stenger et al, 2001). Similarly the findings of this study suggest that close proximity retroelement insertion is a similarly unstable event.…”
Section: Discussionsupporting
confidence: 60%
“…The efficiency of removal through this mechanism is expected to increase with the size of the LTR (Bennetzen, 2005) and also with an inverse of the length of the intervening sequence, and could well be the mechanism behind the removal of close facing retroelement insertions. In humans, Alu repeats constitute 10% of the genome and even though they have a different mechanism of integration to the copialike retroelements, closely spaced and inverted Alu elements are extremely unstable (Lobachev et al, 2000;Rowold and Herrera, 2000;Stenger et al, 2001). Similarly the findings of this study suggest that close proximity retroelement insertion is a similarly unstable event.…”
Section: Discussionsupporting
confidence: 60%
“…A study by Warburton et al identified a number of DNA IRs in the human genome with more than 8 kb in each arm length and 99% identity between the arms (41). In addition, Alu sequences often form DNA IRs with a high degree of homology (Ͼ80%) and substantial alignment (Ͼ275 bp) when present next to each other in the genome (33). Second, a DNA IR also serves either as an "at-risk-motif" or a "fragile site" to regulate large palindrome formation in S. cerevisiae when DNA replication, repair, and checkpoint function are compromised (14,18).…”
Section: Discussionmentioning
confidence: 99%
“…Instability-Multiple studies have demonstrated the particularly unstable nature of nearby TE copies that are in inverted orientation relative to one another [45,70,71]. Closely located, inverted Alu elements are extremely rare in the human genome [66].…”
Section: Inverted Repeats Andmentioning
confidence: 99%